IDO1 induced macrophage M1 polarization via ER stress-associated GRP78-XBP1 pathway to promote ulcerative colitis progression - Gao, Zijian; Shao, Shuai; Xu, Zhen; Nie, Jiao; Li, Chenglin; Du, Chao (Frontiers in Medicine, 2025)
Ulcerative colitis (UC) is a chronic inflammatory bowel disorder distinguished by alternating phases of remission and exacerbation. Restoring immune balance through the modulation of M1 macrophage polarization represents a potentially valuable therapeutic strategy for UC. Indoleamine 2,3-dioxygenase-1 (IDO1) has been shown to contribute to macrophage plasticity, but its role in the pathogenesis of UC via regulating M1 macrophage polarization has not been studied yet. For the clinical component, we analyzed IDO1 expression in UC using bioinformatics analysis of Gene Expression Omnibus (GEO) datasets and validated the result using western blotting of colonic tissues from new recruited UC patients. Colitis was induced in mice via dextran sulfate sodium (DSS) treatment and subsequently treated with oral administration of 1-methyl-DL-tryptophan (1-MT), an inhibitor of IDO1 pathway. The results indicated that IDO1 expression was significantly elevated in UC patients and correlated with M1 macrophage polarization observed in both human data and colitis mice. Furthermore, 1-MT markedly ameliorated DSS-induced weight loss, colonic shortening and disease severity via inhibiting IDO1 expression level, downregulating GRP78-XBP1 pathway and reducing M1 proportion. Notably, in vitro study revealed that overexpressing IDO1 in RAW264.7 cells induced macrophage M1 polarization with increased expression levels of GRP78 and XBP1, which was attenuated by 1-MT treatment. Additionally, the catalytic effect exerted by IDO1 overexpression on M1 polarization was neutralized by employing an inhibitor targeting the endoplasmic reticulum (ER) stress pathway. Thus, our findings suggest that IDO1 may promote UC progression by skewing macrophages towards M1 polarization through ER stress-associated GRP78-XBP1 pathway.